2017
DOI: 10.1002/glia.23174
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte‐derived lipocalin‐2 mediates hippocampal damage and cognitive deficits in experimental models of vascular dementia

Abstract: Lipocalin-2 (LCN2) has diverse functions in multiple pathophysiological conditions; however, its pathogenic role in vascular dementia (VaD) is unknown. Here, we investigated the role of LCN2 in VaD using rodent models of global cerebral ischemia and hypoperfusion with cognitive impairment and neuroinflammation. Mice subjected to transient bilateral common carotid artery occlusion (tBCCAo) for 50 min showed neuronal death and gliosis in the hippocampus at 7 days post-tBCCAo. LCN2 expression was observed predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
152
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(174 citation statements)
references
References 85 publications
10
152
1
2
Order By: Relevance
“…Several studies have shown no significant difference between the cognitive function of wild‐type mice and LCN2 null mice (Table ) . These findings suggest that LCN2 may not have a role in the cognitive process under normal physiological conditions.…”
Section: Lcn2 With Respect To Physiological Condition and Cognitionmentioning
confidence: 87%
See 4 more Smart Citations
“…Several studies have shown no significant difference between the cognitive function of wild‐type mice and LCN2 null mice (Table ) . These findings suggest that LCN2 may not have a role in the cognitive process under normal physiological conditions.…”
Section: Lcn2 With Respect To Physiological Condition and Cognitionmentioning
confidence: 87%
“…Under physiological conditions in a murine model, the expression of LCN2 mRNA and LCN2 protein in the brain appears to be very low to absent . However, only a few studies have reported LCN2 protein expression in the hippocampus, cortex and amygdala of normal mice and the hippocampus of normal adult rats …”
Section: Lcn2 With Respect To Physiological Condition and Cognitionmentioning
confidence: 97%
See 3 more Smart Citations